Prospects of the use of non-traditional vegetable raw materials in the production of confectionery products - Usatyuk, Svitlana; Bozhko, Anastasiia (My University, 2023)
The article is devoted to the study of the state of the confectionery market in Ukraine and the prospects for the use of non-traditional plant raw materials during their production. Confectionery products occupy a significant share in the total volume of the food industry and are characterized by a wide range. The production volume of flour confectionery products is 58% of the total number of confectionery products, and their daily consumption per capita is up to 500 g. The largest share is produced by three Ukrainian confectionery corporations, which entered the annual world ranking of the top 100 Candy Industry in 2022 – the corporation «Roshen», «Millennium» factory, «Konti» company. Non-traditional plant raw materials are increasingly used to enrich food products with useful properties and flavor them in the form of powders, pastes, infusions, sauces. Every year, the assortment of wild fruits, berries and plants, which were not used in Ukraine before, expands significantly. The Google Trends program was used to analyze the popularity of the keyword «sugar-free sweets», comparing the dynamics of «carob» and «cocoa powder». It was established that over the past 5 years, on average, 45-55% of consumers prefer «sweets without sugar», and over the past year three times more often they show a desire to consume products with «carob» than «cocoa powder» in such regions as Kyiv, Lviv, Vinnytsia, Poltava, Dnipropetrovsk regions. The production technology of carob powder includes the following main stages: collecting carob pods, sorting, washing, drying, crushing, dividing into core (10%) and pulp (90%), roasting the pulp at different temperatures, grinding, sieving , packaging. Depending on the temperature conditions of roasting, carob powder is divided into light, medium, and dark types. The hierarchical structure of quality and safety indicators of carob powder consists of normative (organoleptic, physicochemical, microbiological indicators, toxic elements, radionuclides, mycotoxins, pesticides) and non-normative food indicators (proteins, fats, carbohydrates, minerals, vitamins). The analysis of domestic and foreign literary sources on the use of carob powder for the enrichment of confectionery products was carried out. Carob powder is often used as a substitute for cocoa powder, but it is more versatile than cocoa powder.

Статтю присвячено вивченню стану ринку кондитерських виробів в Україні та перспективи використання нетрадиційної рослинної сировини під час їх виробництва. Кондитерські вироби займають значну частку в загальному обсязі харчової промисловості та характеризуються широким асортиментом. Обсяг виробництва борошняних кондитерських виробів становить 58 % від загальної кількості кондитерських виробів, а їх добове споживання на душу населення складає до 500 г. Найбільшу частку виробляють три українські кондитерські корпорації, які ввійшли до щорічного світового рейтингу топ-100 Candy Industry у 2022 році – корпорація «Roshen», фабрика «Millennium», товариство «ВО «Konti». Нетрадиційну рослинну сировину все частіше використовують для збагачення харчових продуктів корисними властивостями та їх ароматизації у вигляді порошків, паст, настоїв, соусів. Щорічно асортимент дикорослих плодів, ягід та рослин, які раніше не використовувалися в Україні, значно розширюється. Використано програму Google Trends для аналізу популярності ключового слова «солодощі без цукру», порівняння динаміки «кероб» та «какао-порошок». Встановлено, що за останні 5 років в середньому 45-55 % споживачів надають перевагу «солодощам без цукру», а за останній рік втричі частіше виявляють бажання споживати вироби з «керобом», ніж «какао-порошком», в таких регіонах як Київська, Львівська, Вінницька, Полтавська, Дніпропетровська області. Технологія виробництва порошку керобу включає такі основні етапи: збирання стручків ріжкового дерева, сортування, миття, сушіння, дроблення, розділення на ядро (10 %) та м’якоть (90 %), смаження м’якоті за різних температурних режимів, подрібнення, просіювання, пакування. Залежно від температурних режимів обсмажування порошок керобу поділяють на типи light (світлий), medium (медіум), dark (темний). Ієрархічна структура показників якості та безпечності порошку керобу складається з нормативних (органолептичні, фізико-хімічні, мікробіологічні показники, токсичні елементи, радіонукліди, мікотоксини, пестициди) та ненормативних харчових показників (білки, жири, вуглеводи, мінеральні речовини, вітаміни). Проведено аналіз вітчизняних та зарубіжних літературних джерел щодо використання порошку керобу для збагачення кондитерських виробів. Найчастіше порошок керобу використовується для заміни какао-порошку, але він є більш поліфункціональним у порівнянні з какао-порошком.
Keywords: confectionery; non-traditional materials; carob; кондитерські вироби; нетрадиційна сировина; кероб; кафедра експертизи харчових продуктів